COVID-19 vaccination hesitancy for children: A pilot assessment of parents in the United States - Kavita Batra; Manoj Sharma; Chia-Liang Dai; Ravi Batra; Jagdish Khubchandani (Tabriz University of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) vaccine hesitancy has remained a significant concern among adults worldwide. However, not much is known about parental vaccine hesitancy for getting children vaccinated for COVID-19 in the U.S. Thus, the purpose of this study was to conduct a national assessment of parents' preferences for COVID-19 vaccination of children using the evidence-based Multi-Theory Model (MTM) and explore the predictors of vaccine hesitancy. Methods: To participate in this study, a national random sample of parents (n=263) took a valid and reliable online questionnaire based on the MTM. Independent samples t test, chi-square test, multiple logistic regression was utilized to analyze data. Results: More than two-fifths (42%) of the participating parents were not willing to get their children vaccinated for COVID-19. Parental vaccination status, booster dose acceptance, education, and political affiliation were significant predictors of willingness to get children vaccinated for COVID-19. In the multiple logistic regression analyses, behavioral confidence and participatory dialogue (i.e., perceived advantages versus disadvantages) were statistically significant predictors of COVID-19 vaccination hesitancy for children among the participating parents. Conclusion: Given the multiple factors that were found influential in parental hesitancy for COVID-19 vaccination among children, multimodal and evidence-based interventions are needed to increase the uptake of COVID-19 vaccines among children by influencing the parents' perceptions, increasing their confidence, dispelling misinformation, and reducing constraints for vaccination. Such interventions should emphasize communication and messaging that is truthful, interactive, scientifically correct, and to be delivered in a variety of community-based settings.